ANCAMAN SAMPAH PLASTIK TERHADAP ORGANISME DI BERBAGAI EKOSISTEM - Khairunisa; Nuzulul Anggi Rizki; Lies Wuryanita Adriyani (Yayasan Nusantara Hasana Berdikari, 2025)
Plastic pollution, particularly microplastics, is a global environmental issue with far-reaching impacts on ecosystems and human health. This review examines the effects of plastics across various ecosystems in Indonesia, including marine, riverine, mangrove, terrestrial, livestock, and human systems. Findings reveal that microplastics are present in fish, zooplankton, corals, and in marine and mangrove sediments. In rivers, plastics contribute to declining local fish populations and hormonal disorders. On land, microplastics inhibit plant growth, disrupt soil structure, and have been detected in chickens and ducks. For humans, microplastic consumption in Indonesia reaches approximately 15 grams per month, with particles detected in the gastrointestinal tract and daily consumables. Such exposure may cause allergic reactions, cell damage, and chronic diseases. These findings highlight that plastic pollution in Indonesia is not only an environmental problem but also a significant public health threat.